EFEKTIVITAS MODEL PBL-STEM DALAM MENDORONG DEEP LEARNING PADA MATERI LAJU REAKSI - Hidayati, Ririn Eva (Balai Diklat Keagamaan Jakarta, 2025)
Students’ understanding of reaction rate concepts in madrasah aliyah remains low due to learning practices that emphasize rote memorization rather than critical and practical thinking. This paper explores the effectiveness of applying the Problem-Based Learning model in conjunction with STEM principles in fostering deep learning among students on the topic of reaction rates. This study employed a quasi-experimental, nonequivalent control-group design. This study involved 68 students from MAN 1 Kota Malang, with 34 assigned to the experimental group (class XI-G) and 34 to the control group (class XI-F). Data collection involved pretests and posttests comprising five-option multiple-choice questions, as well as classroom observations and analysis of student reflection journals. The findings revealed a notable disparity in academic performance between the treatment and comparison groups. The treatment group achieved an average posttest score of 77.33, with an N-Gain of 0.58, placing it in the moderate category. In contrast, the comparison group obtained an average score of 56.67, with a lower N-Gain of 0.28, which was categorized as low. Observational and reflective data indicated that learners in the treatment group were more active, collaborative, and able to transfer concepts to real-world contexts. A key innovation of this study is the structured implementation of the PBL-STEM model, which not only improves cognitive achievement but also fosters deep learning through contextual learning experiences, collaborative projects, and reflective thinking. This model proves to be effective in chemistry instruction aligned with the Merdeka Curriculum. Abstrak Pemahaman siswa terhadap materi laju reaksi di madrasah aliyah masih tergolong rendah karena pembelajaran cenderung berfokus pada hafalan rumus tanpa memberikan ruang untuk berpikir kritis dan aplikatif. Tujuan dari penelitian ini adalah untuk mengevaluasi seberapa efektif penerapan model pembelajaran Problem Based Learning yang terintegrasi dengan pendekatan STEM pada pembelajaran mendalam (deep learning) siswa pada topik laju reaksi. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen dengan desain Nonequivalent Control Group. Sampel penelitian mencakup siswa kelas XI di MAN 1 Kota Malang, dengan XI-F sebagai kelas kontrol dan XI-G sebagai kelas eksperimen, masing-masing berjumlah 34 siswa.Data dikumpulkan melalui pemberian pretest dan posttest dalam bentuk soal pilihan ganda lima opsi, serta melalui teknik observasi dan penulisan jurnal refleksi. Penelitian ini menemukan perbedaan nyata dalam capaian pembelajaran antara kelas eksperimen dan kontrol. Nilai rerata posttest kelas eksperimen adalah 77,33 dengan peningkatan N-Gain 0,58 (kategori sedang), sementara kelas kontrol menunjukkan rata-rata 56,67 dan N-Gain 0,28 (kategori rendah). Data observasi dan refleksi memberi gambaran bahwasanya siswa pada kelompok eksperimen lebih aktif, kolaboratif, dan mampu mentransfer konsep ke situasi nyata. Kebaruan dari penelitian ini terletak pada penerapan sistematis langkah-langkah PBL-STEM yang tidak hanya meningkatkan capaian kognitif, tetapi juga membentuk proses deep learning melalui pengalaman belajar kontekstual, proyek kolaboratif, dan refleksi mendalam. Model ini efektif diterapkan dalam pembelajaran kimia berbasis Kurikulum Merdeka.